Environmental science - Botkin, Daniel B.; Botkin, Daniel B.; Keller, Edward A. (Hoboken, John Wiley, 2014)
Environmental Science: Earth as a Living Planet, Ninth Edition provides emphasis on the scientific process throughout the book and gives readers the structure to develop their critical thinking skills. Updated and revised to include the latest research in the field, the 9th edition continues to present a balanced analytical and interdisciplinary approach to the field.
Appendix A1-A4p.; Glossary G1-G12p.; Index I1-I18p.
Keywords: Ecological restoration; Fossil fuels; Ecosystems